Effect of Methylprednisolone on Capillary Permeability at Surgery under Extracorporeal Circulation - A. P. Kalinichenko; V. V. Lomivorotov; L. G. Knyazkova; I. A. Kornilov (Общая реаниматология, 2011)
Objective: to evaluate the effect of methylprednisolone on capillary leak syndrome at surgery under normothermic cardiopulmonary bypass. Subjects and methods. Twenty-one patients who received intravenous methylprednisolone in a dose of 20 mg/kg body weight after anesthesia induction (a study group) and 21 patients who were not given this agent (a control group) were examined. The investigators estimated the levels of creatinine, albumin, cystatin C, sE-selectin, endothe-lin-1, and glucose in blood, creatinine in urine, microalbuminuria, and blood gas composition and assessed perioperative outcomes. Results. There were statistically significant differences between both groups in microalbuminuria level and albumin/creatinine ratio. At the study stages, there were increases in inotropic support needs, blood venous shunt ratio, and the levels of glucose, endothelin-1, sE-selectin, interleukin-10, and cystatin C and decreases in glomerular filtration rate, PaO2/PAO2 and PaO2/FiO2, and IL-6 level in the methylprednisolone group as compared with the controls. Conclusion. The use of methylprednisolone was not ascertained to reduce the manifestations of capillary leak syndrome. The pulse-dose administration of glucocorticosteroids contributed to the worsening of the signs of endothelial dysfunction (such as an elevated endothelin and sE-selectin levels in the study steps) and negatively affected the recovery of pulmonary and renal functions after cardiopulmonary bypass. Key words: glucocorticosteroids, cardiopulmonary bypass, capillary leak syndrome, endothelial dysfunction.